Social Responsibility of Being Student Leader in General Academic Strand of Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The performance of school children has been studied by considering partial relationships between several personal variables such as the link between cognition and motivation. However, contextual variables, such as a child’s willingness to accept social responsibility, also influence students’ social and academic performance. Thus, students with greater responsibility have a better attitude toward their studies, thereby resulting in higher academic achievement. This study was conducted to find the social responsibility of being a leader of the students. The descriptive research method was used as the research design. This study utilized purposive sampling to gather 50 selected Grade 12 General Academic Strandstudents in the social responsibility of being a leader of the students in terms of classroom management, discipline, and dissemination of information. The study used a survey questionnaire to gather data from the two groups of respondents. The results were 4.15 of the male respondents and 4.13 of the female respondents, which both strongly agreed with the social responsibility of being a leader in terms of classroom management. The result also showed 4.12 for male respondents and 4.22 for female, which both strongly agreed in terms of discipline. The findings showed 4.46 for male respondents and 4.18 for female respondents, which both strongly agreed to the dissemination of information. The overall weighted mean was 4.14 for male respondents and 4.16 for female respondents, which both strongly agreed that the cited variables above are the social responsibilities of being a leader. This paper discussed the results for schools to include programs aimed at improving the social and personal responsibility of being a leader.
Keywords: responsibility attitudes, personal attitudes, reasoned-action, mentoring, secondary education